M.Koshgari's Work” Devonu Lug’oti-T- Turk” and the Issues of Structural-Semantic Analysis (Texas Journal of Philology, Culture and History, 2023)
The article covers the specifics of quantitative expressive vocabulary units and the issues of their expression in the work ”Devonu lug’oti-t- turk”